2014
DOI: 10.1167/iovs.13-13217
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Foveal Cone Specialization and Pit Morphology in Albinism

Abstract: Foveal cone specialization and pit morphology vary greatly in albinism. Normal cone packing was observed in the absence of a foveal pit, suggesting a pit is not required for packing to occur. The degree to which retinal anatomy correlates with genotype or visual function remains unclear, and future examination of larger patient groups will provide important insight on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
159
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(182 citation statements)
references
References 59 publications
16
159
1
6
Order By: Relevance
“…This is not significantly different ( P > 0.05) from normative values published by Wilk et al, who reported cone density at 43.5 μm (approximately 0.15°) eccentricity to be 115,087 cones/mm 2 (95% CI, ±20,311 cones/mm 2 ). 53 In the subjects with Usher syndrome, mean foveal cone density was 69,305 cones/mm 2 (95% CI, ±5656 cones/mm 2 ; Fig. 6), which was significantly reduced compared with both the normal ( P < 0.01) and RP groups ( P = 0.05).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…This is not significantly different ( P > 0.05) from normative values published by Wilk et al, who reported cone density at 43.5 μm (approximately 0.15°) eccentricity to be 115,087 cones/mm 2 (95% CI, ±20,311 cones/mm 2 ). 53 In the subjects with Usher syndrome, mean foveal cone density was 69,305 cones/mm 2 (95% CI, ±5656 cones/mm 2 ; Fig. 6), which was significantly reduced compared with both the normal ( P < 0.01) and RP groups ( P = 0.05).…”
Section: Resultsmentioning
confidence: 86%
“…Horizontal dashed line represents nominally normal foveal sensitivity, 35 dB and above. Vertical dashed lines represent the lowest normal foveal cone density previously reported in the literature 53 : 84,733 cones/mm 2 .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations